Strategies of Language Use in Indonesian Vice Presidential Candidates Debate in the 2024 Election - Zamihu, Juamdan Zamha (Indonesian Journal of EFL and Linguistics, 2024)
Understanding the language use strategies in political debates helps candidates craft their communication strategies strategically. Candidates need to resonate with voters, address their concerns, and effectively communicate their vision for the nation through their language and communication style. The objective of the study is to provide a comprehensive description of the strategies of language use in the Indonesian vice presidential candidates debate in the 2024 election to construct their identities, to frame issues in a particular way, to manipulate information to gain an advantage over their opponents, to establish authority and credibility, to persuade voters, and to present themselves in a certain light. It used content analysis to understand the main issues addressed and the candidates' stances on the issues. The data were collected by transcribing spoken content from video and audio recordings and then analyzed using thematic analysis, consisting of familiarization, generating themes, review, refinement, and defining and naming themes. The results showed that all three candidates aimed to project an image of trustworthiness and competence, but each used different techniques to achieve it. Muhaimin Iskandar focused on experience and continuity, Gibran on pragmatism and youth appeal, and Mahfud on intellectual authority and good governance. The choice of language was crucial to their strategies. Muhaimin Iskandar's populism resonated with rural voters, while Gibran's modern vocabulary appealed to the urban youth. Mahfud's academic tone established him as a knowledgeable figure.